Rogue aid?: The determinants of China's aid allocation - Dreher, Axel; Fuchs, Andreas (CESifo working papers, 2011)
Foreign aid from China is often characterized as "rogue aid" that is not guided by recipient need but by China's national interests alone. However, no econometric study so far confronts this claim with data. We make use of various datasets, covering the 1956-2006 period, to empirically test to which extent political and commercial interests shape China's aid allocation decisions. We estimate the determinants of China's allocation of project aid, food aid, medical teams and total aid money to developing countries, comparing its allocation decisions with traditional and other so-called emerging donors. We find that political considerations are an important determinant of China's allocation of aid. However, in comparison to other donors, China does not pay substantially more attention to politics. In contrast to widespread perceptions, we find no evidence that China's aid allocation is dominated by natural resource endowments. Moreover, China's allocation of aid seems to be widely independent of democracy and governance in recipient countries. Overall, denominating aid from China as "rogue aid" seems unjustified. -- aid allocation ; China's foreign aid ; new donors ; donor motives
Keywords: 1956-2006; Arbeitspapier; Graue Literatur